NGS-based BRCA1/2 mutation testing of high-grade serous ovarian cancer tissue: results and conclusions of the first international round robin trial - Endris, Volker; Stenzinger, Albrecht; Pfarr, Nicole; Penzel, Roland; Schirmacher, Peter (Virchows Archiv, 2016)
With the approval of olaparib as monotherapy treatment in platinum-sensitive, relapsed high-grade serous ovarian cancer by the European Medical Agency (EMA), comprehensive genotyping of BRCA1 and BRCA2 in tumor tissue has become a mandatory pre-therapeutic test. This requires significant advances in routine tumor test methodologies due to the large size of both genes and the lack of mutational hot spots. Classical focused screening approaches, like Sanger sequencing, do not allow for a sensitive, rapid, and economic analysis of tumor tissue. Next-generation sequencing (NGS) approaches employing targeted panels for BRCA1/2 to interrogate formalin-fixed and paraffin-embedded tumor samples from either surgical resection or biopsy specimens can overcome these limitations. Although focused NGS methods have been implemented by few centers in routine molecular diagnostics for the analysis of some druggable oncogenic mutations, the reliable diagnostic testing of the entire coding regions of BRCA1 and BRCA2 was a new challenge requiring extensive technological improvement and quality management. Here, we describe the implementation and results of the first round robin trial for BRCA1/2 mutation testing in tumor tissue that was conducted in central Europe on May 2015, shortly after the approval and prior to the official release of olaparib. The high success rate of 81 % (21/26 test centers) demonstrates that BRCA1/2 multicenter mutation testing is well feasible in FFPE tumor tissue, extending to other tumor entities beyond ovarian cancer. The high number of test centers passing the trial demonstrates the success of the concerted efforts by German, Swiss, and Austrian pathology centers to ensure quality-controlled NGS-based testing and proves the potential of this technology in routine molecular pathology. On the basis of our results, we provide recommendations for predictive testing of tumor tissue for BRCA1/2 to clinical decision making in ovarian cancer patients.